Effects of endothelin-1 on intracellular tetrahydrobiopterin levels in vascular tissue - Cerrato, R; Crabtree, M; Antoniades, C; Kublickiene, K; Schiffrin, E; Channon, K; Böhm, F (Taylor and Francis, 2018)
Objective: Tetrahydrobiopterin (BH4) is the essential cofactor of endothelial nitric oxide synthase (eNOS) and intracellular levels of BH4 is regulated by oxidative stress. The aim of this paper was to describe the influence of exogenous endothelin-1 on intracellular BH4 and its oxidation products dihydrobiopterin (BH2) and biopterin (B) in a wide range of vascular tissue. Design: Segments of internal mammary artery (IMA) and human saphenous vein (SV) from 41 patients undergoing elective surgery were incubated in ET-1 (0.1 μM). Aorta and lung from transgenic mice overexpressing ET-1 in the endothelium (ET-TG) were analysed with regards to intracellular biopterin levels. Human umbilical vein endothelial cells (HUVEC) were incubated in ET-1 (0.1 μM) and intracellular biopterin levels were analysed. From 6 healthy women undergoing caesarean section, subcutaneous fat was harvested and the resistance arteries in these biopsies were tested for ET-mediated endothelial dysfunction. Results: In HUVEC, exogenous ET-1 (0.1 μM) did not significantly change intracellular BH4, 1.54 ± 1.7 vs 1.68 ± 1.8 pmol/mg protein; p = .8. In IMA and SV, exogenous ET-1(0.1 μM) did not change intracellular BH4 n = 10, p = .4. In aorta from wild type vs ET-TG mice there was no significant difference in intracellular BH4 between the groups: 1.3 ± 0.49 vs 1.23 ± 0.3 pmol/mg protein; p = .6. In resistance arteries (n = 6) BH4 together with DTE (an antioxidant) was not able to prevent ET-mediated endothelial dysfunction. Conclusion: ET-1 did not significantly alter intracellular tetrahydrobiopterin levels in IMA, SV, HUVEC or aorta from ET-TG mice. These findings are important for future research in ET-1 mediated superoxide production and endothelial dysfunction.